Lasertechniques treatment of vascular malformations - Poetke, M.; Urban, P.; Berlien, H.-P. (Phlebologie, 2010)
Vascular malformations are structural abnormalities, errors of vascular morphogenesis, which can be localized in all parts of the vascular system. All vascular malformations by definition, are present at birth and grow proportionately with the child; their volume can change. In contrast to the haemangiomas, which only proliferate from the endothelial cells the division in stages is of clinical importance. Vascular malformations are divided from the part of vascular system, which is affected.In principle the techniques of laser application in congenital vascular tumours like haemangiomas and in vascular malformations are similar, but the aim is different. In tumours the aim is to induce regression, in vascular malformations the aim is to destroy the pathologic vascular structure because there is no spontaneous regression. This means that the parameters for treatment of vascular malformations must be more aggressive than for vascular tumours.
Keywords: Vascular tumours; vascular malformations; Nd: YAG laser; flashlamp pumped-pulsed dye laser